Adoption and impact of tissue culture bananas in Burundi: an application of a propensity score matching approach - Ouma, Emily A.; Dubois, T.; Kabunga, N.; Nkurunziza, S.; Qaim, M.; Asten, Piet J.A. van (CAB International, 2013)
Pests and diseases are among the main reasons for low banana productivity in smallholder farming systems in the central African highlands, where the crop is an important staple, In parts of Rwanda, Burundi and North and South Kivu provinces of eastern Democratic Republic of Congo, diseases such as banana bunchy top virus and banana Xanthomonas wilt are prevalent, thereby creating a large demand for new planting material and improved varieties that may have higher yield combined with resistance to diseases or nematodes. To improve the productivity of banana (Musa spp), access by farmers to improved pest- and diseasefree planting material is fundamentaL Traditional methods of propagating bananas using suckers serve to perpetuate the problem of pests and diseases, thereby reducing production even further, Banana plantlets obtained from tissue culture (TC) technology are potentially disease-free alternatives but remain largely inaccessible to most smallholder farmers due to the high cost of plantlets, This study employs a propensity score matching technique to examine the adoption and impact of TC banana technology in Burundi using a sample of 313 banana-farming households, In Burundi, TC bananas are subsidized by FAO and non-government organizations (NGOs), thus providing free plantlets to farmers, However, the adoption of TC bananas has not resulted in any significant increment in banana productivity or gross margins compared with traditional propagation using suckers, Improvements in institutional factors related to the delivery of technology and improvement of TC plantlet quality seem to be preconditions for more favourable technology impacts.